RIFM fragrance ingredient safety assessment, butyl 10-undecenoate, CAS Registry Number 109-42-2. (August 2019) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Francis, M.; Fryer, A.D.; et al.
Abstract: Butyl 10-undecenoate was evaluated for genotoxicity, repeated dose toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data from read-across analog methyl undec-10-enoate (CAS # 111-81-9) show that butyl 10-undecenoate is not expected to be genotoxic. Data on butyl 10-undecenoate and read-across analog methyl undec-10-enoate (CAS # 111-81-9) show that butyl 10-undecenoate is not a safety concern under the current, declared levels of use for the skin sensitization endpoint. The repeated dose, reproductive, and local respiratory toxicity endpoints were evaluated using the TTC for a Cramer Class I material, and the exposure to butyl 10-undecenoate is below the TTC (0.03 mg/kg/day, 0.03 mg/kg/day, and 1.4 mg/day, respectively). The phototoxicity/photoallergenicity endpoints were evaluated based on UV spectra; butyl 10-undecenoate is not expected to be phototoxic/photoallergenic. The environmental endpoints were evaluated; butyl 10-undecenoate was found not to be PBT as per the IFRA Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., PEC/PNEC), are <1. Highlights: Butyl 10-undecenoate; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.